Analisis Penentuan Harga Pokok Produksi berdasarkan Metode Full Costing di Rumah Makan D’garazi Balikpapan - Lau, Trivonia; Prihanisetyo, Adi (STIE PENA, 2024)
In this current era of the globalization and free trade has brought changes to the business sector in Indonesia. One of the impacts on the domestic industry is the tight competition which is growing rapidly that must be faced between business men and women. Therefore, the purpose of this study is to analyze the determination of HPP based on the full costing method in D’Garazi restaurant and to determine the comparison of HPP in determining the selling price between the full costing method and the HPP calculation of D’Garazi restaurant. The method used in this study is a qualitative method with the type of case study research. Data collections techniques in this study are through observation, interviews, and documentations. The research results show that D’Garazi restaurant in calculating the HPP still use a very simple method in accordance with the understanding of the owner. The calculated costs do not include all costs spend. The cost of all supporting material is not calculated, and the depreciation cost has not been calculated either. Keywords: cost of production, full costing method, selling price